Transcriptomic Analysis Reveals a Bifurcated Terephthalate Degradation Pathway in Rhodococcus sp. Strain RHA1 - Hara, Hirofumi (American Society for Microbiology, 2007)
Phthalate isomers and their esters are important pollutants whose biodegradation is not well understood. Rhodococcus sp. strain RHA1 is notable for its ability to degrade a wide range of aromatic compounds. RHA1 was previously shown to degrade phthalate (PTH) and to have genes putatively encoding terephthalate (TPA) degradation. Transcriptomic analysis of 8,213 genes indicated that 150 were up-regulated during growth on PTH and that 521 were up-regulated during growth on TPA. Distinct ring cleavage dioxygenase systems were differentially expressed during growth on PTH and TPA. Genes encoding the protocatechuate (PCA) pathway were induced on both substrates, while genes encoding the catechol branch of the PCA pathway were additionally induced only on TPA. Accordingly, protocatechuate-3,4-dioxygenase activity was induced in cells grown on both substrates, while catechol-1,2-dioxygenase activity was induced only in cells grown on TPA. Knockout analysis indicated that pcaL, encoding 3-oxoadipate enol-lactone hydrolase and 4-carboxymuconolactone decarboxylase, was required for growth on both substrates but that pcaB, encoding β-carboxy-cis,cis-muconate lactonizing enzyme, was required for growth on PTH only. These results indicate that PTH is degraded solely via the PCA pathway, whereas TPA is degraded via a bifurcated pathway that additionally includes the catechol branch of the PCA pathway.